NATURAL ZEOLITES AS MANURE ADDITIVE: THE ADVANTAGES AND DISADVANTAGES - Lenny Marilyn Estiaty; Dewi Fatimah; Dadan Suherman; Kamaludin Alamsyah (Jurnal Zeolit Indonesia, 2005)
Research has been done to evaluate the addition of zeolite to manure fertilizer. This research is aimed to review the advantages and disadvantages of zeolites as manure fertilizer additive. Investigation is carried out by different variables: zeolite particle size, zeolite concentration and curing time. The results show that zeolite particle sizes of